Low Circulating Levels of Neurotensin in Women with Nonalcoholic Fatty Liver Disease Associated with Severe Obesity. Issue 2 (25th December 2017) - Auguet, Teresa; Aragonès, Gemma; Berlanga, Alba; Martínez, Salomé; Sabench, Fàtima; Aguilar, Carmen; Villar, Beatriz; Sirvent, Joan Josep; Del Castillo, Daniel; Richart, Cristóbal
Abstract : Objective: This study was performed to investigate neurotensin plasma levels in patients with nonalcoholic fatty liver disease (NAFLD) associated with severe obesity. Methods: The plasma levels of neurotensin in 20 women with normal weight and 51 women with morbid obesity (MO) were measured, and women were subclassified according to their hepatic histology as having MO without NAFLD ( n = 18) or MO with NAFLD ( n = 33). The NAFLD group included 15 women with simple steatosis (SS) and 18 women with nonalcoholic steatohepatitis (NASH). To quantify neurotensin in plasma, a multiplex sandwich immunoassay with a Luminex magnetic bead–based platform was used. Results: Neurotensin levels were significantly decreased ( P = 0.001) in women with MO and NAFLD (3.62 ± 0.85 ng/mL), compared with women with MO and normal liver function (11.65 ± 1.95 ng/mL; P = 0.001) and women with normal weight (13.68 ± 2.58 ng/mL; P = 0.001). There was no difference in levels between women with SS and women with NASH ( P = 0.415). Conclusions: Circulating levels of neurotensin were decreased in women with NAFLD associated with MO.